The mediation effect of anthropometry and physical fitness on the relationship between birthweight and basal metabolic rate in children. (22nd December 2020) - Nobre, Isabele Goes; Moura-dos-Santos, Marcos Andre; Nobre, Gabriela Goes; Santos, Ravi Marinho dos; da Costa Ribeiro, Isabella; Carvalho Jurema Santos, Gabriela; da Silva da Fonseca, Eveline Viana; Santos de Oliveira, Tafnes Laís P.; Ferreira e Silva, Wylla Tatiana; Nazare, Julie-Anne; Leandro, Carol Gois
Abstract: Background: Birthweight (BW) has been associated with anthropometry, body composition and physical fitness during growth and development of children. However, less is known about the mediation effect of those variables on the relationship between BW and basal metabolic rate (BMR) in children. Objective: To analyse the mediation effect of anthropometry, body composition and physical fitness on the association between BW and BMR in children. Methods: In total, 499 children (254 boys, 245 girls) aged 7–10 years were included. Anthropometry (weight, height, head, waist and hip circumferences), body composition (skinfolds thickness, body fat percentage), physical fitness (handgrip strength, flexibility, muscular endurance, muscular explosive power, agility, running speed) and BMR were evaluated. The analyses were conducted by: single-mediator analysis (SMA) and multi-mediator analysis (MMA). Results: The SMA indicates height, head, waist and hip circumferences and handgrip strength as significant mediators of BW on BMR for boys and height, hip circumference and handgrip strength as significant mediators of BW on BMR for girls. In MMA for girls, there were significant indirect effects for height, hip circumference and handgrip strength, with 79.08% of percent mediation. For boys, the head and waist circumferences mediation had a significant indirect effect, with 83.37% of percent mediation. Conclusion: The anthropometric variables associated with BW were body height, head, hip and waist circumferences for boys and body height and hip circumference for girls. The current study provides new evidence that height and handgrip strength during childhood mediated the relationship between BW and BMR.